2000
DOI: 10.1034/j.1600-0773.2000.pto870504.x
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance Responding Following Amphetamine‐Induced Dopamine Depletion

Abstract: The effect of an amphetamine‐induced depletion of striatal dopamine on active and passive avoidance responding of rats was examined. Sixteen animals received two sets of 4 injections each of 15 mg/kg d‐amphetamine, administered at 2 hr intervals with each set delivered one week apart. One week after the last injection, animals were given 50 consecutive active avoidance trials in a shuttle box. Animals treated with amphetamine exhibited a 50% depletion of striatal dopamine and showed a slower learning curve, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Our results expand upon earlier studies that demonstrated slower avoidance learning after pharmacological striatal DA depletion in rats (Halladay et al 2000). Our finding, that 2WAA is absent in vrDD mice when DA signaling is restored to the striatum alone, but intact when restored to both amygdala and striatum, is strong evidence for an interaction of DA signaling in these two brain regions.…”
Section: Discussionsupporting
confidence: 77%
“…Our results expand upon earlier studies that demonstrated slower avoidance learning after pharmacological striatal DA depletion in rats (Halladay et al 2000). Our finding, that 2WAA is absent in vrDD mice when DA signaling is restored to the striatum alone, but intact when restored to both amygdala and striatum, is strong evidence for an interaction of DA signaling in these two brain regions.…”
Section: Discussionsupporting
confidence: 77%